Dynamic metabolic regulation of histone modifications during the yeast metabolic cycle - Bárbara Guzmán-Dinamarca; Raúl Conejeros; Marcelo Rivas-Astroza (PLoS ONE, 2025)
Eukaryotes achieve a wide range of stable phenotypes by virtue of epigenetic modifications. However, what drives epigenetic diversification in the first place remains an open question. Here, we investigated the dynamic interplay between the production fluxes of epigenetic cosubstrates and histone post-translation modifications (PTMs) in Saccharomyces cerevisiae’s Yeast Metabolic Cycle (YMC). We developed a novel approach integrating flux analysis with transcriptomic data to investigate the production fluxes of acetyl-CoA and SAM and their influence on histone marks H3K9Ac and H3K4me3. Our results show that acetyl-CoA and SAM flux dynamics are asynchronous during the YMC, suggesting distinct regulatory roles. Gene ontology analysis revealed that genes whose enrichment of H3K9Ac correlates with acetyl-CoA dynamics are associated with metabolic functions, while genes whose enrichment of H3K4me3 correlates with SAM dynamics are associated with translation processes. Finally, we found evidence that chromatin accessibility on genes promoter regions was a precondition for the metabolic fluxes influencing the enrichment of H3K4me3 and H3K9Ac. These findings support the concept that metabolism provides timely cosubstrates essential for histone PTMs.